Implementasi Program ASMARA: Pemberdayaan Kesehatan Masyarakat di PKH Kapanewon Jetis, Bantul, Yogyakarta - Asyfa Inayatul Faizah; Zulkipli Lessy (Universitas Pahlawan Tuanku Tambusai, 2023)
This research examines the implementation of Independent Family Hope Health Agency or ASMARA program which aims to facilitate and bring health services to Beneficiary Families (KPM) in the program called Family Hope Program (PKH). Implementation of the program is carried out through three stages, namely coordination, socialization, and implementation. At the coordination stage, a cooperation between PKH Kapanewon Jetis and the Jetis 1 and 2 Health Center (Puskesmas) was carried out to procure blood pressure equipment and training. Through this collaboration with external parties, the need for blood pressure equipment and health check equipment can be fulfilled. The socialization stage was carried out to provide understanding and training to the participants of PKH. This socialization involves the Health Center and PPM UIN Sunan Kalijaga students. The participants of PKH received an explanation about the purpose, benefits, and the usage of blood pressure devices and other health check tools. The implementation phase of the program is carried out routinely every month by conducting health checks using a blood pressure monitor and checking blood sugar, level of cholesterol as well as Hb. The results of examinations are documented for monitoring and following-up. An inspection fee is charged to the KPM to maintain program continuity. The implementation of the ASMARA program aims to facilitate access, increase KPM awareness about the importance of routine health checks, and involve KPM actively in the program. This program fits the concept of health empowerment which was recommended forward by WHO to improve the overall and sustainable level of public health.